Analisis Rasio Keuangan dan Corporate Social Responsibility Terhadap Nilai Perusahaan Pada Perusahaan Yang Terdaftar di BEI - angelina chrisnawati; Khadijah Khadijah (eCo-Buss, 2022)
This research aims to test whether the effect of profitability, solvency, and corporate social responsibility on the firm value on energy subsector companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 - 2020. The population in the study was 67 companies. The selected research sample with purposive sampling consisted of 8 companies. Based on the results of the t test which showed that partially profitability has a positive and significant influence on the value of the company with (6,035) > 2,028), solvency has a positive and significant influence on the value of the company with (-3,384) > (2,028), and Corporate Social Responsibility has a positive and significant influence on the value of the company with (5,182) > (2,028). Based on f test results or simultaneously showed that profitability, solvency, and corporate social responsibility had a positive and significant influence on the value of the company, with (33,690) > (2,866). The value of R Square (square R) in this study is 0.737, this shows that the variables of profitability, solvency, and CSR to the company's value are 73.7% while the remaining 26.3% is influenced by other variables outside the study.